Induction of the PPARγ (Peroxisome Proliferator-Activated Receptor γ)-GCM1 (Glial Cell Missing 1) Syncytialization Axis Reduces sFLT1 (Soluble fms-Like Tyrosine Kinase 1) in the Preeclamptic Placenta. Issue 1 (July 2021) - Armistead, Brooke; Kadam, Leena; Siegwald, Emily; McCarthy, Fergus P.; Kingdom, John C.; Kohan-Ghadr, Hamid-Reza; Drewlo, Sascha
Abstract : Preeclampsia is a hypertensive disorder of pregnancy that is a major cause of maternal-fetal morbidity and mortality worldwide. Severe preeclampsia (sPE) is mediated by pathology of the placental villi resulting in repressed PIGF (placental growth factor) production and hyper-secretion of sFLT1 (soluble fms-like tyrosine kinase 1), the net effect being wide-spread maternal endothelial dysfunction. Villous trophoblast differentiation is under control of the PPARγ (peroxisome proliferator-activated receptor γ) and GCM1 (glial cell missing 1) axis which is dysregulated in sPE. We hypothesized that disruption of trophoblast differentiation via the PPARγ-GCM1 axis is a major contribution to excess production of sFLT1 and pharmacological activation of PPARγ in the sPE placenta could reduce sFLT1 to normal levels. sPE, age-matched control placentas and first-trimester villous explants, were used to investigate the molecular relationships between PPARγ-GCM1 and sFLT1. We modulated this pathway by pharmacological activation/inhibition of PPARγ using Rosiglitazone and T0070907, respectively, and through siRNA repression of GCM1. PPARγ and GCM1 protein expressions are reduced in the sPE placenta while FLT1 protein and sFLT1 secretion are increased. GCM1 reduction in the first trimester explants significantly increased sFLT1 secretion, suggesting GCM1 as a key player in this pathway. Activation of PPARγ restored GCM1 and significantly reduced sFLT1 expression and release in first trimester and sPE placental villi. Functional integrity of the PPARγ-GCM1 axis in the villous trophoblast is critical for normal pregnancy development and is disrupted in the sPE placenta to favor excessive production of sFLT1. Pharmacological manipulation of PPARγ activity has the potential to rescue the antiangiogenic state of sPE and thereby prolong pregnancy and deliver improved clinical outcomes. Abstract : Supplemental Digital Content is available in the text.